2016
DOI: 10.1007/s40092-016-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

JIT single machine scheduling problem with periodic preventive maintenance

Abstract: This article investigates a JIT single machine scheduling problem with a periodic preventive maintenance. Also to maintain the quality of the products, there is a limitation on the maximum number of allowable jobs in each period. The proposed bi-objective mixed integer model minimizes total earliness-tardiness and makespan simultaneously. Due to the computational complexity of the problem, multi-objective particle swarm optimization (MOPSO) algorithm is implemented. Also, as well as MOPSO, two other optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Notwithstanding, human reliability has potentials of deepening and changing our insights of maintenance workforce optimisation. However, the literature is awaiting this fulfilment (see Shahriari et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, human reliability has potentials of deepening and changing our insights of maintenance workforce optimisation. However, the literature is awaiting this fulfilment (see Shahriari et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Khatab et al (2014) have used the genetic algorithms for optimization of selective maintenance of multi-mission systems. In (Shahriari et al 2016), authors have investigated the problem of just-in-time single machine with a cyclic preventive maintenance. In another work, Adeyeri and Mpofu (2017) have developed a system decision support tools for interactive trends monitoring and maintenance in a competitive environment.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Significant amount of research on allocating limited resources to competing tasks has been reported ( Vanhoucke 2013;Naber and Kolisch 2014;Xu and Feng 2014;Shahriari 2016;Hashemin and Fatemi Ghomi 2012;Garmsiri and Abassi 2012;Yaghoubi et al 2013;Dao et al 2017;Noori-Darvish and Tavakkoli-Moghaddam 2012;Shahriari et al 2016;Ighravwe et al 2016;Garmdare et al 2017). Bulk of this research falls under the general area of Operations Research.…”
Section: Introductionmentioning
confidence: 99%